2003
DOI: 10.1038/sj.leu.2402879
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the treatment of chronic phase and advanced phase CML and Philadelphia chromosome positive ALL

Abstract: Chronic myeloid leukaemia (CML) is a malignant disease of the bone marrow characterised by the presence of the Philadelphia (Ph) chromosome. About 20% of acute lymphoblastic leukaemia (ALL) patients also show this genetic abnormality. A new drug, imatinib (Glivec s , Novartis Pharma AG, Basel, Switzerland, and formerly STI571) is having a profound effect on the treatment and management of all stages of CML and Philadelphia chromosome positive (Ph+) ALL. New treatment algorithms are being developed. Should imat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Recent studies revealed that this agent also inhibits kinases other than ABL, such as platelet-derived growth factor receptor (PDGFR) and KIT, and that it is effective for a variety of hematologic and nonhematologic malignancies. 1 A variety of adverse events including cytopenia, nausea, vomiting, edema, myalgia, diarrhea, rash, fatigue, and anorexia have been reported in the context of phase I-III trials in chronic myelocytic leukemia (CML) and phase II trials in gastrointestinal stromal tumors (GIST), 2 while most patients tolerate it at clinically effective doses. Herein, we describe a patient with CML who developed severe ocular complication during treatment with imatinib.…”
Section: To the Editormentioning
confidence: 99%
“…Recent studies revealed that this agent also inhibits kinases other than ABL, such as platelet-derived growth factor receptor (PDGFR) and KIT, and that it is effective for a variety of hematologic and nonhematologic malignancies. 1 A variety of adverse events including cytopenia, nausea, vomiting, edema, myalgia, diarrhea, rash, fatigue, and anorexia have been reported in the context of phase I-III trials in chronic myelocytic leukemia (CML) and phase II trials in gastrointestinal stromal tumors (GIST), 2 while most patients tolerate it at clinically effective doses. Herein, we describe a patient with CML who developed severe ocular complication during treatment with imatinib.…”
Section: To the Editormentioning
confidence: 99%
“…30 Acute leukaemia-type chemotherapy Once people develop a myeloid or lymphoid blastic transformation, acute leukaemia-type chemotherapy can be used as a debulking or cytoreductive treatment prior to treatment with other agents including SCT; this therapy generally produces a HR in the region of 40%. 55 …”
Section: Introductionmentioning
confidence: 99%
“…1 The Bcr/Abl kinase signals to a variety of downstream survival pathways, including the mitogenactivated protein kinase kinase (MEK)/extracellular signalregulating kinase (ERK) cascade, Akt, signal transducers and activators of transcription (STATs), and nuclear factor B (NF-B), among others. [2][3][4] Activation of these pathways in Bcr/Abl ϩ cells results in increased expression of several antiapoptotic proteins, such as Bcl-xL.…”
Section: Introductionmentioning
confidence: 99%